Implementación historial clínico electrónico (2017)
Nowadays, health care providers, whether private or public, have the obligation to keep a medical history of each of their patients, which must be electronic according to Law 1438 of 2011, where the minimum requirements must also be taken into account by the Colombian laws. All of the above is established in order to guarantee the provision of a good and safe quality service in which the patient's information can be accessed not only at the local level but also at the national level, for this reason health institutions were obliged to acquire and implement a system of electronic medical history that will be adapted to their needs and requirements before 2013. In addition to the aforementioned information, the patients' information must be properly treated since the information obtained is private and "Health information is classified internationally as high risk and must have all legal and technological protections.